Connecting rural India to the world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Connecting rural India to the world, New York Times, May 2000 Embalam, India - In this village at the southern tip of India, the century-old temple has two doors.